An open comparative study of nail drilling as adjunctive treatment for toenail onychomycosis*. (2nd September 2016) - Shemer, A.; Gupta, A. K.; Amichai, B.; Farhi, R.; Baran, R.; Daniel, C. R.; Daigle, D.; Foley, K. A.
Abstract: Introduction Novel treatment regimens are being developed to improve drug penetration through the nail plate. This study investigated the efficacy of nail drilling regimens for the treatment of onychomycosis.Methods Participants were assigned to holes with combination (oral plus topical terbinafine) therapy (Group 1), holes with topical terbinafine (Group 2) or topical terbinafine only (Group 3). Measurement of clear nail and mycology was performed at baseline and at weeks 4, 10, 16, 22 and 28. Mixed linear models were used to compare mean percent clear nail. Mycological cure rates were also tabulated for each group. Tolerability and adverse events were documented.Results Ninety-eight participants were enrolled (106 nails). Both groups with holes had significantly higher percentage of clear nail compared with topical terbinafine alone. Although no significant difference between the two groups where holes were drilled in the nail plate, Group 1 demonstrated improvement over Group 3 earlier than Group 2 (visit 2 versus visit 4). Group 1 also had the highest mycological cure rates.Conclusion Treatment with holes plus topical terbinafine produces significantly greater improvement in toenails' appearance and higher mycological cure rates compared to treating the dorsal aspect of the nail plate with topical terbinafine alone.